A review on the coupling of cooling, desalination and solar photovoltaic systems. (July 2015) - Byrne, Paul; Fournaison, Laurence; Delahaye, Anthony; Ait Oumeziane, Yacine; Serres, Laurent; Loulergue, Patrick; Szymczyk, Anthony; Mugnier, Daniel; Malaval, Jean-Luc; Bourdais, Romain; Gueguen, Hervé; Sow, Ousmane; et al.
Abstract: Single cooling and desalination technologies require a high amount of energy to produce cooling and fresh water, respectively. Coupling these systems seems to be attractive not only to reduce their energy consumption rates and to gain more flexibility in operation but also for environmental considerations. Besides, using solar energy to drive these coupled systems appears also interesting. The major increases in cooling and desalination demands occur in locations where solar energy is abundant. This article reviews the latest research works on systems able to carry out cooling and/or desalination using solar energy. The ability of coupling desalination technologies to cooling systems is investigated. A heat pump can produce cooling energy at the evaporator and heat at the condenser for a membrane distillation unit. An ice slurry process can operate with sea water. It freezes only pure water that can be separated from the liquid. A comparison of these systems is made. Membrane distillation (MD) and ice slurry systems must improve to be as efficient as standard technologies. An intelligent energy and water production management will have to be developed to control the operation of a system coupling ice slurry, MD and solar photovoltaic energy.